2017
DOI: 10.4254/wjh.v9.i36.1332
|View full text |Cite
|
Sign up to set email alerts
|

Hospital contacts with alcohol problems prior to liver cirrhosis or pancreatitis diagnosis

Abstract: AIMTo evaluate prior hospital contacts with alcohol problems in patients with alcoholic liver cirrhosis and pancreatitis.METHODSThis was a register-based study of all patients diagnosed with alcoholic liver cirrhosis or pancreatitis during 2008-2012 in Denmark. Hospital contacts with alcohol problems (intoxication, harmful use, or dependence) in the 10-year period preceding the diagnosis of alcoholic liver cirrhosis and pancreatitis were identified.RESULTSIn the 10 years prior to diagnosis, 40% of the 7719 alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…For instance, 11% of patients with ALD cirrhosis in Denmark are only diagnosed at death. 25 However, we find it unlikely that the observed time trends were influenced by either code validity or undetected ALD, since coding practices and the proportion of undetected ALD have remained stable during the ICD-10 era. 15 In our previous study, we found a somewhat stable ALD incidence, but forecasted a future decrease driven by progressively lower incidence rates in the birth cohorts born after 1960.…”
Section: Calendar Yearmentioning
confidence: 73%
See 1 more Smart Citation
“…For instance, 11% of patients with ALD cirrhosis in Denmark are only diagnosed at death. 25 However, we find it unlikely that the observed time trends were influenced by either code validity or undetected ALD, since coding practices and the proportion of undetected ALD have remained stable during the ICD-10 era. 15 In our previous study, we found a somewhat stable ALD incidence, but forecasted a future decrease driven by progressively lower incidence rates in the birth cohorts born after 1960.…”
Section: Calendar Yearmentioning
confidence: 73%
“…Despite the improved prognosis, the mortality associated with ALD is still very high, and the fact that over two-thirds of patients have end-stage liver disease (cirrhosis) at the time of diagnosis tells us that there is further potential to reduce the overall mortality by earlier intervention. We have previously found that 40% of patients who are diagnosed with ALD cirrhosis have at least one prior hospital contact with alcohol problems (alcohol intoxication, harmful alcohol use, or alcohol dependence) within a 10-year period 25 and that the risk of ALD cirrhosis increases with the number of these contacts. 42 So naturally, hospital contacts with alcohol problems are a potential point of early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and risk stratification are regarded as being key to improving the prognosis of patients with CLD 3,35,36 . Health care professionals should ensure that risk factors are identified and followed up at all contacts.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…An estimated 5-10% of patients with alcohol overuse develop severe alcohol-related liver fibrosis, making alcohol the main reason for advanced liver disease [2]. The average severe alcohol-related liver disease (ALD) patient has been in contact with the healthcare system for alcohol-related problems at the time up to diagnosis [3,4]. This provides ample opportunities for earlier disease detection during the up to 15 years of asymptomatic disease progression [3,5].…”
Section: Introductionmentioning
confidence: 99%